Quilombolas e desenvolvimento sustentável: análise a partir da comunidade Capoeira dos Negros (Macaíba/RN) - Macedo, Rayana Garcia de (2014)
Quilombo communities remaining are groups marked by insufficient public assistance and characterized by living in rural and conducting economic activities such as agriculture. The development on a sustainable basis is important to ensure strategies for economic growth and environmental preservation. This work aims to study the remaining Quilombo Capoeira Black community, located in the municipality of Macaíba, Rio Grande do Norte, considering the principles of sustainable development. Attempt to respond to what level such community can be considered sustainable from an analysis of their social practices. The methodological procedures used consisted of a literature review and documentary, questionnaires, conducting semi-structured interviews and direct observation. The final results show that the family farm has characteristics that approximate the principles of sustainable development, including the diversification of labor, food production with less environmental damage and strengthening the rural environment, and indicate that the main economic activities practiced in Capoeira dos Negros community are agriculture, manufacturing of cassava flour and brick manufacturing, which, in turn, are linked to negative environmental impacts, such as sedimentation pond, groundwater contamination, air pollution and soil erosion. What lead to the conclusion that the social practices of the community are not in line with the dimensions of sustainable development. It is hoped that the survey results provide subsidies for development and implementation of public policies